Potensi Peran Fitokimia Apigenin dalam Pencegahan dan Pengobatan Kanker: Literature Review - Syahrina Zulianti (Lembaga Pengembangan Kinerja Dosen, 2025)
Degenerative diseases such as cancer have a significant impact on overall health and are a leading cause of death worldwide. Identifying phytochemicals with potential preventive and therapeutic properties is crucial in combating these diseases. Apigenin, a flavonoid phytochemical, has garnered attention due to its potential role in cancer prevention and treatment. Therefore, the aim of this research is to prioritize an approach to cancer treatment based on more effective and fewer side effects. Apigenin, a plant-derived flavonoid, has received significant scientific consideration for its potential health-enhancing effects through modulation of inflammation, oxidative stress, and various other biological activities. This review utilizes online scientific articles from reputable platforms such as PubMed, Google Scholar, and Springer Link. The objective of this research is to explore the potential role of apigenin as a promising phytochemical in cancer prevention and treatment, elucidating its therapeutic mechanisms and future research directions.